FOSTERING REAL WORLD SKILLS IN CHILDREN THROUGH INTERACTIVE LEARNING APPS - Tjhin, Santo; Mahamaya, Benning; Lim, Jocelyn; Ingrid, Samantha (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
Magodang is an innovative application designed for children aged 8–14, as well as their parents and educators, aiming to develop real-world skills and build student portfolios. In an increasingly competitive educational landscape, portfolios are essential for showcasing students' academic and professional journeys. However, many students, including those who are homeschooled or have special needs, face significant challenges in accessing skill development programs. Magodang addresses these barriers by connecting users with workshops, competition preparation programs, coaching sessions, and certifications through a user-friendly platform enriched with gamification features. The application provides personalized program recommendations, intuitive navigation, and collaborative tools that empower parents and educators. These features help parents identify programs aligned with their children’s interests and assist educators in integrating extracurricular activities into classroom settings. The research employs the Semantic Literature Review (SLR) method, descriptive qualitative analysis, and the Design Thinking framework to create an interactive and relevant platform. Tools such as Miro, Figma, and Google Forms are used for ideation, prototyping, and surveys. The findings demonstrate that Magodang enhances student engagement, fosters collaboration among stakeholders, and addresses gaps in traditional education systems. It provides a practical solution for early skill development, creating an inclusive and accessible educational environment for all learners.